Juozapas Legavičius (Józef Legowicz, 1743–1812): His Life and Legacy - Girininkaitė, Veronika (Senoji Lietuvos literatūra, 2017)
This paper outlines the biography of priest Juozapas Antanas Legavičius (Józef Antoni Legowicz, 1744–1812) and introduces his creative legacy. A graduate of Vilnius Jesuit Academy and doctor of theology, he wrote more than ten didactic books that were published in Vilnius from 1776 to 1808. The research is based on the manuscripts found in the Vilnius University Library and on several papers by Polish scholars. The fate and the content of the extant books of this author are briefly reviewed. Some valuable biographical facts were revealed in the process of research, and data on Legavičius’s remaining books was gathered. Two books previously thought to be anonymous – Kapłan sluga Boży i pasterz dusz (1793) and Pienia swięte (1801) – were attributed to him. Mention is also made of Juozapas Legavičius’s active role in rebuilding the church in Karkažiškė and in establishing and maintaining the parochial school.
Keywords: Juozapas Legavičius; Józef Legowicz; Vilnius Jesuit Academy; the Enlightenment; preaching; education